MEMPREDIKSI ARUS KAS DENGAN LABA BERSIH DAN TOTAL PENDAPATAN KOMPREHENSIF LAIN - Dabella Yunia; Master Irfan Ibrahim (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
The objective of this research is to predict future cash flow by current net income and current total comprehensif income. This research is quantitatif research. Analysis test performed using a simple regression model by Statistical Product and Service Solutions (SPSS) 24. The result of this research give evidence that curret net income dan total comprehensif income is usefull to predict fuure cash flow. Current net income dan total comprehensif income predictable for future net income.